The Effect of R.A.F.T Strategy and Anxiety upon Writing Competency of The Seventh Grade Students of SMP Negeri 3 Mengwi in Academic Year 2013/2014 - ., NI MADE ELIS PARILASANTI; ., Drs. I Wayan Suarnajaya,MA., Ph.D.; ., Drs. Asril Marjohan,MA (Universitas Pendidikan Ganesha, 2014)
This research aimed at investigating the effect of RAFT strategy and anxiety upon writing competency. It was an experimental research with 2x2 factorial design. The result showed that (a) there was significant difference in writing competency between the students taught by RAFT strategy and those taught by conventional strategy,b) there was an interactional effect between the implementation of RAFT strategy and the students? anxiety, (c) there was significant different in the writing competency between the students? with high anxiety, taught by RAFT strategy and those who are taught by conventional technique, (d) there was significant different in the writing competency between the students? with low anxiety, taught by implementing RAFT strategy and those who are taught by conventional strategykeyword : anxiety, RAFT strategy, writing competency.